Clinical outcomes of adjacent 1 segregation in a familial translocation t(8;18)(p21.3;p11.23). Issue 6 (June 1996) - Cockwell, A E; James, R S; Moore, I E; Hatchwell, E; Crolla, J A
Abstract : We report a reciprocal translocation t(8;18)(p21.3;p11.23) in which both unbalanced products of adjacent 1 segregation were observed within a family. The proband was originally referred because of short stature and a webbed neck, but further investigations showed that she had mental retardation and a congenital heart defect, and had inherited an unbalanced form of the maternal translocation, 46, XX, der(8)t(8;18)mat. The proband's sister spontaneously aborted an 11 week fetus with multiple major system malformations, which was found to have a 46, XY, der(18)t(8;18)mat karyotype. The phenotypic findings of the affected subjects are discussed.